Point‐of‐care ultrasound diagnosis of a pyogenic liver abscess in the emergency department. Issue 2 (1st April 2021) - McClure, Matthew B.; Patel, Kishan; Cabrera, Gabriel; Kalivoda, Eric J.
Abstract: Pyogenic liver abscess (PLA) is a rarely encountered condition in the emergency department (ED) that necessitates a timely diagnosis by the emergency physician. An early ED diagnosis is challenging as the presenting symptoms of PLA are often variable and nonspecific. The rapid bedside diagnosis of PLA with point‐of‐care ultrasound (POCUS) performed by emergency physicians has not been investigated thoroughly. This case report describes the expeditious identification and ED management of PLA by implementing emergency physician‐performed POCUS as the initial diagnostic modality.